2020
DOI: 10.1002/jwmg.21988
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Behaviors of Hunted Mule Deer During Rifle Season

Abstract: Animal populations face increased threats to mobility and access to critical habitat from a variety of human disturbances including roads, residential development, agriculture, and energy development. Disturbance from human hunting is known to alter habitat use in ungulates, but recent work suggests that hunting may also trigger the onset of migration. Whether this holds true across ungulate species and hunting systems warrants further empirical testing. We used global positioning system location data from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
(192 reference statements)
0
4
0
Order By: Relevance
“…Performance of individually selected models were assessed by the concordance statistic. Across both species, the concordance statistic of individual models ranged from 0.57 to 0.81 (mean 0.67 ± 0.06 for both species) which is adequate compared to other studies – for example Stewart et al [ 68 ] reported concordance between 0.594 and 0.647 while Rodgers et al [ 69 ] had concordances between 0.749 and 0.910. Model concordance was higher in saturated models for all bar one fish (where the final model had concordance 4 × 10 − 16 higher), thus by performing model selection via AIC to avoid over parameterising our individual models, concordance may have suffered.…”
Section: Discussionmentioning
confidence: 54%
“…Performance of individually selected models were assessed by the concordance statistic. Across both species, the concordance statistic of individual models ranged from 0.57 to 0.81 (mean 0.67 ± 0.06 for both species) which is adequate compared to other studies – for example Stewart et al [ 68 ] reported concordance between 0.594 and 0.647 while Rodgers et al [ 69 ] had concordances between 0.749 and 0.910. Model concordance was higher in saturated models for all bar one fish (where the final model had concordance 4 × 10 − 16 higher), thus by performing model selection via AIC to avoid over parameterising our individual models, concordance may have suffered.…”
Section: Discussionmentioning
confidence: 54%
“…Our analysis included only adult females, which limited our inference given that male and female mule deer can move and select habitat differently (Rodgers et al., 2021 ). For instance, males often have larger home ranges than females (Relyea et al., 2000 ), potentially increasing risk of exposure to CWD via greater encounter rates with infected individuals and/or contaminated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has revealed a diversity of migratory movement patterns for mule deer and highlighted the challenges for effective management caused by the oversimplification of migratory movements using classification strategies (van de Kerk et al, 2021). Hidden Markov movement models can ameliorate this problem by examining the daily drivers of movement states (defined by step lengths and turning angles) using additional covariates without relying on an a priori set of movement classes, thereby providing a more expansive look at the responses of mule deer to important drivers such as weather, hunting pressure, forage quality and exposure to development (Lendrum et al, 2012; Monteith et al, 2011; Rodgers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%